Breast Cancer in Thi-Qar 2018, it's determinants, histopathological presentation and six years' time trends, A comparative study - A. Habeeb, Estabraq; J. Hassan, Alaa; N. Musa, Hameed (University of Thi-Qar Journal of Science, 2019)
Objectives : to assess the soscio-demographic characteristics, clinico-pathological presentations, and important determinant of breast cancer patients counseling breast disease center in Thi-Qar 2018, to study and compare the yearly time trend of breast cancer in Thi-Qar from 2013-2017.Methods: A cross sectional analytical design was used. all women presented with breast mass at defined age, at the time of study, were included.Results: About (59.5%)of malignant masses were moderately differentiated and (32%) of them were poorly differentiated (8.5%) were well differentiated at the time of study, Also about half of patients presents at late stages, while only 10% at early stages , in other word. The age was strongly correlated factor and about 57.5% of the malignancies were above 45.Recommendations : 1.Further studies with different design permit longer duration, are required and preferred to be follow-up type to determine the effect of confound risk factors as age, stress and radiation rather than defined ones, also studies required about response to therapy and follow the complication. 2.Regular programmed screening required to detect the cancer in the earlier stage, and facilitate the availability of screening tools at the health care centers and in peripheries hospitals of Thi-Qar.